Pengaruh Penggunaan Learning Management System Terhadap Hasil Belajar Siswa Pada Pembelajaran Daring SMK Negeri 3 Salatiga - Septian Adi Prasetyo; Rissal Efendi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
This quantitative research aims to determine the effect of the use of the Learning Management System on student learning outcomes of SMK Negeri 3 Salatiga. The sample of this research was 36 people. Data collection techniques using observation and questionnaires. The analysis technique used is simple linear regression with a significance level of α = 5% (0.05). Based on the results of the research, the simple linear test calculation of t statistics obtained a significance of 0.000 and a tcount of 6.920, this shows that there is an effect of the use of the Learning Management System on Learning Outcomes. Based on these calculations, it can be concluded that the use of the Learning Management System has an effect on student learning outcomes of SMK Negeri 3 Salatiga.